Orientasi dan Strategi Pemasaran dalam Menciptakan Keunggulan Posisional serta Dampaknya terhadap Kinerja Perguruan Tinggi - Soegoto, Agus Supandi (Jurnal Trikonomika, 2011)
The aim of is this research is to analize the influence of market orientation, marketing strategy, and positional advantage on university performance, partially and simultaneously. Population of this research is the Private Universities (PTS), and the unit of analysis is the PTS in Kopertis IV. The number of samples taken from 470 PTS in the Kopertis IV; 45 universities, 4 institutes, 237 colleges, 153 academies and 31 polytechnics. Sampling conducted by stratified random sampling technique. Analyzed the influence of the model using structural equation models (SEM). The results of this research has relevance in explaining conformity between variables. The results indicate that market orientation, marketing strategy, positional advantage, and university performance in the moderate category. Market orientation and marketing strategy, has a significant relationship. Market orientation and marketing strategies simultaneously influential and partial of positional advantage, which influence the marketing strategy is more dominant. Market orientation, marketing strategy, and positional advantage have simultaneously influence on university performance, in which partially it was more determined by positional advantage.